EXISTENTIAL CRISIS OF THE INDIVIDUAL AND SOCIAL IN COMMUNICATIVE PRACTICES OF THE POSTMODERN ERA - Ordenov, Serhii (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2024)
Introduction. The crisis is the most complex social phenomenon, associated with processes of social stagnation, anomie, increased tension, and conflict within society. The aim and tasks. This article aims to undertake a philosophical reflection on the existential crisis of the individual and social within communicative practices of the postmodern era. Research methods. The research methodology encompasses historical and comparative approaches combined with the phenomenological method, as well as philosophical principles of objectivity, systematicity, and the progression from the abstract to the concrete, among others. Research results. The crisis states of contemporary society are characterized by their fluidity, multiplicity, and non-linearity, leading to the uncertainty and instability of social structures. These, along with the specific features of postmodern culture, determine the specific forms of communicative practices in the social and political life of society. In particular, in the communicative practices of the postmodern era, such marginalized subcultural forms of life construction as minimalism, downshifting, and post-truth are affirmed. Discussion. Modern individuals despair in the gradual progress of reason in history, as a result of which the influence of the irrational in their lives is intensified. The reason for this lies in the fact that the economic development of the world economy has led to a disproportion of the moral and the rational in humanity’s life. The utilitarian rationality of the capitalist consumer society, which is subject to its internal mechanisms and principles of expediency (yet can be irrational and destructive towards the society and the individual within it), creates contradictory types of behavior and communicative practices both in the life of society as a whole and in the life of the individual. Conclusions. All this leads to the third (extreme) form of human alienation (alienation of the individual from their human essence), the destruction of the social continuum, thereby causing an existential crisis of the individual and social in the postmodern era.